ISIS From the dark fiction of Hollywood - Yousef , Kinda (Re-visiones, 2024)
Does the word “Medieval” describe a group that is competing with the world’s best high-tech producers of images such as Hollywood? In times of globalization, images are playing a relevant role in shaping both opinions and identities. The images of terror that we see today, released by the group ISIS, are part of our modern world. Hollywood has been generating a new stereotype of the „Orient“ and of “Muslims” for decades, and it seems to have arrived at a real life version of its own stereotype. The images of ISIS have a lot in common with the ones of Hollywood: Image quality and propagandistic techniques on one hand. The adoption of a stereotype as a representative image on the other hand. The collaboration Hollywood-Pentagon and/or Hollywood-Washington has its roots since the early days of the Hollywood film industry. In many critical moments in history, this collaboration could reshape public opinion in the US. This propaganda reached its darkest point with the film Zero Dark Thirty (2012). Today’s world’s worst enemy “ISIS” is a consequence of some of the worst decisions taken in our times. It represents a dark image of the modern world that, for the first time, we are seeing beyond the screens of Hollywood’s blockbusters.